Dr. Adler [Rabbi Dr. Nathan Marcus] (Tufts Archival Research Center, 2008)
2.5 x 4.25. Produced by: The London Stereoscopic & Photographic Company. 110 & 108, Regent Street and 54, Cheapside. These dates are approximate.